(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article describes investigated in recent years explicit aims and objects of linguistics in functional grammar and pragmastylistic, as well as the manifestation and use of them on social networks. Attention is drawn to thefunction and pragmatic side of the process of conversation in a social network, and the impact of the conversation on the sender in different social groups in society. The function and pragmatics of speech activity in the social network is represented by reference circuits. Social network is not only for the functions of communication and information dissemination, but also shows an internal goal and task pragmatics of the process.